Situation Report: Romania, 26 June 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Press and Printing Committee Established Publishing Policy Becomes more Restrictive The Writers' Union Awards for 1974 Foreign Minister Visits Egypt Todor Zhivkov's Visit to Romania Administrative Change Involving Former Party Official Gheorghe Apostol